Distributism 2.0: Putting Holiness Back in Commercial Society - Robson, Gregory (American catholic philosophical quarterly, 2025)
This article examines how and how far distributism is compatible with socialism and capitalism and how distributist political economy might enhance the holiness of society. After preliminaries on Christianity and political economy, I describe distributism in the light of Pope Leo XIII’s encyclical Rerum Novarum (1891) and suggest that distributism is incompatible with traditional socialism. After this I consider the potential compatibility of distributism and a version of capitalism, first indicating inadequacies in G. K. Chesterton's and Hilaire Belloc's understandings of capitalism. The article then argues that distributist capitalism is achievable if and because holiness in a life is often supported by wealth, but that wealth need not include productive property. A wealth-based conception of distribution that is fit for modern commercial society, which I call Distributism 2.0 (or "distributalism"), emphasizes attending to God's will in the day-to-day decisions that together constitute the bulk of the life of any person or business.